Religious Harmony Based on Spiritual and Intellectual Journey of René Guénon - Hinggis, Yulafa; Fauzan, Aris; Haji Abdul Karim, Norhayati binti (Pascasarjana IAIN Pontianak, 2024)
This article explores the intellectual and spiritual journey of René Guénon, who traversed the spiritual experiences of various religions in the world such as Catholicism, Hinduism, Taoism, and ended up in Islam. It seems that Guénon did not see the conversion of religion as a contradictory process, but rather as a continuous stage that enriched his search for the true truth. The position of this research is one of the testimonies of René Guénon's important role in developing religious harmony. Although many writings talk about religious harmony, the presence of René Guénon emphasizes ideas and works about the life of religious harmony. This article seeks to answer the question of the urgency of René Guénon’s spiritual and intellectual journey in crossing and upholding the essential values of the religion studied. This type of qualitative research focuses on library research, with a biographical approach. Furthermore, the sources in this study refer to direct works written by René Guénon and other authors who discuss René Guénon. The results of this study show that the essential values of each religion supported by spiritual and intellectual maturity are an important foundation for living a harmonious life between religious people.